2017
DOI: 10.30827/tsg-gsw.v7i13.5525
|View full text |Cite
|
Sign up to set email alerts
|

Family interaction and social stigmatization of people living with HIV and AIDS in Puerto Rico

Abstract: This article aims to describe the manifestation of HIV stigma in the family context and how this could impact the life of people living with HIV (PLWH). The data derive from a larger phenomenological study addressing manifestations of stigma in the lives of PLWH when interacting with the health sector. Nine focus groups were carried out in 2011 with PLWH  (N=67). Eight themes emerged from the qualitative analysis. For the purpose of this article, we focus on the categories related to family dynamics: the negot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This sense of family support and close relationships emphasized by familism may be protective for health and health behaviors [14][15][16]. However, in some instances such as when the behavior is stigmatized (e.g., HIV testing), people may feel hesitant to seek support from familial networks [17,18].…”
Section: Familism and Hiv Testingmentioning
confidence: 99%
“…This sense of family support and close relationships emphasized by familism may be protective for health and health behaviors [14][15][16]. However, in some instances such as when the behavior is stigmatized (e.g., HIV testing), people may feel hesitant to seek support from familial networks [17,18].…”
Section: Familism and Hiv Testingmentioning
confidence: 99%
“…On the other hand, this prevents and undermines the provision of support from anyone who could be in a good position to remind them when it is time to take treatment. Most studies indicate that adherence to ART can be aided through the use of family and social support [35][36][37][38][39][40][41]. Hornschuch et al [34] reported that PLWH mentioned different reminder methods during ART treatment including alarms, medication charts, family members, and friends.…”
Section: Discussionmentioning
confidence: 99%
“…PLWH mentioned that when they visit their relatives, they do not take treatment because they tend to laugh at them and, as a result, they do not like visiting other people. The stigma attached to PLWH can be brought by both family members of the affected person and the society around them [39][40][41][42][43][44]. It is based on this reason that many PLWH may not disclose to family, friends and other community members in fear of being stigmatised and isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, HIV/AIDS patients have faced stigmatization, which is a negative experience caused by the disease (Zhang et al, 2021). The relevant literature shows that stigmatization is most frequently encountered in mental illnesses and other conditions including addiction, AIDS, tuberculosis, obesity, cancer and disability (Bogart et al, 2019; Craig et al, 2017; Kudva et al, 2020; Matthews et al, 2017; Puhl et al, 2020; Rivera‐Díaz et al, 2017; Shiri et al, 2018). According to the data from the Joined Nations Program on HIV/AIDS, 34.6% of the people aged 15–49 in Angola, a country in southwestern Africa, discriminate against and stigmatize the HIV‐positive people (UNAIDS, 2019).…”
Section: Introductionmentioning
confidence: 99%